2022
DOI: 10.1038/s41598-022-10621-1
|View full text |Cite
|
Sign up to set email alerts
|

Unemployed individuals contact GPs more frequently but report lower satisfaction: results of the population-based DEGS1 and the GPCare-1 patient survey

Abstract: Unemployment is associated with a variety of adverse health-related outcomes, yet little data on primary care services for this risk group exist. Using data from two surveys, we analyzed the frequency of GP contacts and patients’ experiences with GPs comparing unemployed with employed individuals. Data of the German Health Interview and Examination Survey for Adults (DEGS1), a nationwide cross-sectional study (n = 8151), were analyzed regarding associations between employment status and the number of GP visits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
2
1
Order By: Relevance
“…No significant differences in levels of satisfaction with providers were found in relation to sociodemographic factors. In contrast to many studies carried out worldwide, a study conducted in Germany by Ikar et al (2022) showed that unemployed individuals were less satisfied with doctors in PHC centers. Also, another study conducted by Franjo et al (2020) in Croatia revealed that patients between 26 and 40 years old were less satisfied with providers in PHC centers.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…No significant differences in levels of satisfaction with providers were found in relation to sociodemographic factors. In contrast to many studies carried out worldwide, a study conducted in Germany by Ikar et al (2022) showed that unemployed individuals were less satisfied with doctors in PHC centers. Also, another study conducted by Franjo et al (2020) in Croatia revealed that patients between 26 and 40 years old were less satisfied with providers in PHC centers.…”
Section: Discussioncontrasting
confidence: 75%
“…In contrast to many studies carried out worldwide, a study conducted in Germany by Ikar et al. (2022) showed that unemployed individuals were less satisfied with doctors in PHC centers. Also, another study conducted by Franjo et al.…”
Section: Discussionmentioning
confidence: 75%
“…Particular attention should therefore be paid to loneliness with additional support from employers and the government to improve health and well-being. Similarly, Ikar et al (2022) link unemployment to health. They compared the frequency of contact with GPs and patients' experiences of GPs among unemployed and employed people by using data from two surveys.…”
Section: Introductionmentioning
confidence: 99%